Exploring Green Research Opportunities Within the Fintech Landscape for Sustainable Growth - Lak lak Nazhat El Hasanah (Start-up and Financial Technology, 2025)
Objective: This research aims to identify green research opportunities in fintech and develop a conceptual framework to support sustainable growth in the financial sector. Research Design & Methods: This research uses a Systematic Literature Review (SLR) approach to collect, analyze, and evaluate relevant literature related to fintech, green finance, and sustainability from various reputable sources within the span of 2015-2024, with strict selection criteria to identify research gaps and develop an in-depth conceptual framework. Findings: The study highlights the important role of FinTech in improving transparency, efficiency, and accountability in green finance, such as through green bonds and sustainable investment platforms. Fintech also expands financial inclusion, empowering diverse stakeholders to participate in the green economy. However, challenges such as data privacy, cybersecurity, regulatory gaps, and limited accessibility for smaller companies hinder its full potential. Overcoming these barriers requires multi-stakeholder collaboration, standardized data practices, and the development of green competencies. Implications & Recommendations: These findings underscore the need for strong policy and industry collaboration to optimize the role of FinTech in sustainable finance. Investments in green competencies and innovative regulatory frameworks are recommended to enable the seamless integration of FinTech into green initiatives. Future research should explore the interactions between green job creation and FinTech advancements to advance sustainable development goals. Contribution & Value Added: This research contributes to the understanding of the transformative potential of FinTech in achieving sustainable economic growth.